Consumer Legal Protection for Whitening Cream Cosmetic Products - Arlina, Sri; Syafrinaldi, Syafrinaldi; Mufidi, Faiz (Magister Hukum Universitas Semarang, 2024)
This research aims to determine the implementation of the principles of justice and supervision of consumer protection in protecting consumers who use whitening cream cosmetic products (from the perspective of legal justice theory). The urgency of this research was initiated because many whitening cream products are circulating that contain dangerous ingredients and are sold at low prices. The research involved takes a juridical-normative approach. Techniques for data collection include literature studies and observations at BPOM Pekanbaru City. The principle of justice in consumer legal protection has not been effectively implemented by Article 2 paragraph (2) of the UUPK. One of the factors is a lack of effective compensation. The government merely issues administrative and criminal sanctions without being obliged to compensate for damages or restore the health of the skin affected by products. Then, according to UUPK rules, the BPOM does not have the authority to supervise the execution of consumer protection (Article 30 (1) UUPK). As a result, the Pekanbaru City BPOM's supervisory function on this research issue is ineffective, leaving consumers with insufficient facilities and infrastructure, free legal aid, and quick access to settle consumer disputes with business actors.